2013
DOI: 10.1177/1758834013499637
|View full text |Cite
|
Sign up to set email alerts
|

New combinations and immunotherapies for melanoma: latest evidence and clinical utility

Abstract: Until recently there was no effective systemic therapy for metastatic melanoma. Increased understanding of tumor biology and immune regulation has led to the development of drugs targeting the mitogen-activated protein kinase (MAPK) pathway (BRAF inhibitors and MEK inhibitors) and T-cell regulation (CTLA4 antibodies). These drugs are the new standard of care, however barriers to better patient outcomes include limited responses and significant toxicities (CTLA4 antibodies) and lack of durability in the majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…Immune checkpoint inhibitors are revolutionizing the ability to treat metastatic cancer (15)(16)(17)(18). Many clinical trials are under way using these agents to treat a variety of cancers, and inhibitors of CTLA-4 and PD-1 have been approved for melanoma (19).…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint inhibitors are revolutionizing the ability to treat metastatic cancer (15)(16)(17)(18). Many clinical trials are under way using these agents to treat a variety of cancers, and inhibitors of CTLA-4 and PD-1 have been approved for melanoma (19).…”
Section: Discussionmentioning
confidence: 99%
“…Here we focused on the potential role of immunotherapy as an alternative therapeutic strategy, one that has been used with some success in melanoma (11,41). Next to nothing is known about the effects of the signaling pathway alterations seen in differentiated thyroid cancers on the immune antigens of the thyroid cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several advances in immunotherapeutic strategies over recent years especially in treating melanoma (10,11); however, immunotherapy as a treatment for thyroid cancer has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting either PD-1 or PD-L1 can stimulate the immune system and enhance the T-cells' ability to lyse tumor cells. This axis could also be a very promising therapeutic target for mucosal melanoma as patients with cutaneous melanoma, who participated in recent studies and were administered antibodies against the PD-1/PD-L1 pathway, showed high response rates with longer survival [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%